THE SCIENTIFIC BASIS AND METHODOLOGY FOR INTEGRATED ASSESSMENT OF NATURAL CONDITIONS AND RESOURCES FOR ORIENTATION OF THE DEVELOPMENT OF OFFSHORE WATERS AND ISLANDS, APPLY TO TRUONG SA ARCHIPELAGO - Tuan, Tran Anh (Vietnam Journal of Marine Science and Technology, 2014)
The integrated assessment of natural conditions and resources to orient for the development of offshore waters and islands is a new field of research that has not been much interested in Vietnam. First of all, due to the characteristics of offshore waters and islands, applying the assessment process and methods that was carried out successfully on the territory is also difficult for these sea areas. The study of the scientific basis and methodology of integrated assessment of natural conditions and resources to orient for the development of offshore waters and islands should be done first to create a favorable premise for further researches. This paper presents some fundamental issues in integrated assessment to orient for the development of offshore waters and islands, apply to Truong Sa archipelago, in which focus on establishing of the system of marine landscape classification for study area, analyzing of potentials, limitations and important components of the Truong Sa archipelago that should be considered in the assessment process as well as the establishment of a system of criteria and assessment process.